Analisis Beban Kerja Fisik dan Mental Pada Operator Contact Center (Studi Kasus : PT. XYZ Samarinda) - Lina Dianati Fathimahhayati; Lilis Anggrainy; Willy Tambunan (Program Studi Teknik Industri Universitas Setia Budi, 2019)
The work requirements of the contact center operator in PT. XYZ Samarinda to always be friendly to customers in any circumstances and have to focus on work is likely to cause mental workload. In addition, the contact center operator must work monotonously by sitting in front of the computer within 8 hours can cause physical workload. Based on these problems, a study was conducted on the analysis of physical and mental workload on the contact center operators so that recommendations could be given to improve productivity and comfort while working. Measurement of physical workload is done using the %CVL measurement method at work. While the measurement of mental workload was carried out using the NASA-TLX method by distributing questionnaires to 9 contact center operators for 10 days. The results showed that the average physical workload of contact center operators was 13.5%. These results indicate that the physical workload of contact center operators is included in the low category, which means there is no significant burden. While the average mental workload of contact center operators is 65. Based on these results, the mental workload value of contact center operators is in the moderate category. Recommendations for improvements that can be given are doing the right way to sit, making improvements to the layout of the air conditioner so that the work environment becomes comfortable and using an ergonomic work chair. In addition it is necessary to build a good relationship that is by understanding the communication style between workers so that misunderstandings cannot be occur, conduct small celebrations, recreation, and hold ESQ Training to balance emotions and intelligence.